Isotopes and new norms: Investigating the emergence of early modern U.K. breastfeeding practices at St. Nicholas Kirk, Aberdeen. (19th June 2018) - Britton, K.; McManus‐Fry, E.; Cameron, A.; Duffy, P.; Masson‐MacLean, E.; Czére, O.; Smith, N.; Stones, J.; Winfield, A.; Müldner, G.
Abstract: In this study, we aim to extend the chronological, geographical, and societal scope of previous bioarchaeological research on infant diet and age at weaning in Britain in the past through the analysis of the large medieval and post‐medieval skeletal assemblage from St. Nicholas Kirk, Aberdeen, Scotland. Stable carbon and nitrogen isotope data were obtained from rib collagen from 67 sub‐adults across the two phases and were compared with mean adult female dietary isotope values. Nitrogen isotope data were modelled using the R Package WARN, along with previously published data sets, to provide quantitative age estimates for the commencement and completion of weaning at St. Nicholas Kirk and other medieval and post‐medieval sites. Data from Phase A (12th–15th century AD) suggest that breastfeeding may have continued up to and beyond the age of 2 years, likely in combination with other foods. This complements previously published data from urban and rural medieval contexts in England, highlighting similarities in infant feeding practices across very different contemporary populations. Data from post‐medieval Phase B at St. Nicholas Kirk (15th–18th century AD) give new insights into early modern period breastfeeding and weaning practices, indicating that weaning commenced soon after birth and was completed relatively early (within a year). These data bridge the gap between previously published studies on medieval and late 18th‐ to 19th‐century populations from the British Isles and suggest that trends observed at later urban sites may be rooted in preceding centuries, although the underlying reasons for this change are difficult to elucidate. Contributing factors may include the social and religious changes that occurred in the post‐reformation period, such as the decrease in the use of wet nurses, changes in the availability and acceptability of artificial feeding, increased urbanism, and even changes in the socio‐economic status of those interred in the Kirk.